IFN-γ auto-antibody: An overview as one of the autoimmunity effect - Ika Krisnawati, Dyah; Rahayu, Dwi; Rinawati, Fajar; Susilowati, Erna; Santoso, Puguh; Darmayanti, Rofik; Puspitasari, Betristasia; Yunarsih, Yunarsih; Sucipto, Sucipto; -Rong Kuo, Tsung (Trends in Immunotherapy, 2024)
Interferon Gamma (IFN-γ) plays a vital role in normal immune surveillance and possesses immunomodulatory, antimicrobial, and anticancer properties. It stands as the exclusive type II IFN, and its production is regulated by cytokines released by Antigen-Presenting Cells (APCs), particularly interleukin (IL)-12 and IL-18. These cytokines act as a connecting link between infection and IFN-γ production in the innate immune response. The functional IFN-γ receptor (IFNGR) consists of two ligand-binding IFNGR1 chains and two signal-transducing IFNGR2 chains, along with associated signaling machinery. Both IFNGR1 and IFNGR2 chains belong to the class II cytokine receptor family, characterized by ligand binding in the small angle of a V formed by the two Ig-like folds in the extracellular domain. Autoantibodies targeting interferon-gamma (IFN-γ) can lead to immunodeficiency and are linked to various opportunistic infections. The immunopathogenesis is associated with the neutralizing activity of these autoantibodies on the IFN-γ signaling pathway, resulting in the blocking of certain immune responses activated by IFN-γ. This review provides a concise overview of IFN-γ Autoantibody detection, the immunopathogenesis of related diseases, and potential treatment options.